A cross-sectional study on awareness and knowledge of menstrual hygiene practices among college going girls in Coimbatore district, Tamil Nadu - Rajan, Palani Vel; Shanmugam, Jeevithan; Jayaraj, Navee Prabhu; Arumugam, Archana (International Journal Of Community Medicine And Public Health, 2020)
Background: Women in India are restricted in their daily activities and mobility due to taboos, cultural barriers associated with menstruation and menstrual practices. Poor menstrual hygiene can make them susceptible to various reproductive tract infections. In this study we assessed the awareness, knowledge of menstruation and practice of menstrual hygiene among adolescents. Methods: A college based cross-sectional study was conducted in the field practice area of an urban health training centre (UHTC) of a tertiary care hospital in the district of Coimbatore. Universal sampling method was used for selection of participants. A structured proforma was used for data collection. Microsoft excel 2007 was used for data entry and data analysis was done using SPSS version 27. Results: It was found that 80.4% had formal education on menstrual hygiene. 94.5% of them had the habit of changing pads/cloths before they go to bed. 94.1% had the habit of washing with water every time and 76.49% of those who had the habit of washing used soap/antiseptic while washing. Conclusions: Knowledge about menstruation and menstrual hygiene should be provided in schools and colleges. Ensuring availability of sanitary products, water, privacy and appropriate waste disposal in all public services and institutions can address the challenges.